STUDY OF THE UTILIZATION OF FUNCTIONAL FACILITIES IN THE FISHERIES PORT OF THE ARCHIPELOGI SUNGAILIAT PROVINCE OF BANGKA BELITUNG - Osta Lumban Tobing; Bustari Bustari; Polaris Polaris (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTFish production landed in Sungailiat VAT in 2017 was 4,419,520, kg while in 2018 an increase of 4,936,332 kg from the data showed that the Sungailiat port had a large potential for capture fisheries. However, the great potential of fisheries has not been supported by optimal port facilities and maximum management, some of the facilities in Sungailiat VAT are not functioning such as ice picking facilities, fish packing or storage buildings and fishing nets or fishery resting buildings. This study aims to determine the condition and level of utilization of functional facilities. This research was conducted in May 2019 at PPN Sungailiat. The method used in this study is a survey method, by observing and collecting data directly about the utilization of Sungailiat VAT functional facilities, the utilization level analysis is used to determine the level of functional facility utilization. The results obtained by the level of utilization of functional facilities in Sungailiat PPN which can be counted only 3 facilities namely, freshwater facilities (SWRO), the utilization rate is 11.27% (very underutilized), the utilization rate of electricity installation facilities is 79.24% (utilized with good), while the level of utilization of BBM facilities is 40.34% (sufficiently utilized properly). These results can be concluded that the level of functional facilities utilization in Sungailiat PPN is still classified as not good. there is a need for better port development planning to restore untapped facilities such as ice factories, fish packing and storage buildings as well as fishing nets and resting buildings.Keywords: functional facilities,archipelago fishing port sungailiat, level of utilization